Mengukur kepercayaan masyarakat atas kinerja Kementerian ATR/BPN melalui analisis sentimen pada platform digital - Reza Nur Amrin; Ridho Darman; Asih Retno Dewi; Sudibyanung Sudibyanung (Widya Bhumi, 2026)
Governments increasingly leverage social media for institutional reputation management, yet a significant gap often persists between institutional narratives and public perception. This study aims to analyze the topical and sentimental disparities between the Instagram posts of Indonesia’s Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) and netizens' responses throughout 2023. Employing a quantitative approach, this research applies lexicon-based sentiment analysis and descriptive content analysis to 15,198 comments across 1,213 posts. The results reveal a striking digital communication paradox. While the institutional agenda is heavily dominated by the celebration of land certificate handovers and ministerial visits, 56.5% of public comments exhibit negative sentiment. Netizens actively repurpose the comment section into a grassroots grievance mechanism for agrarian disputes, bureaucratic hurdles in land certification, and reports of land mafias. Consequently, there is a diametrical clash in the contextualization of the core lexicons "land" and "certificate" between the glorification of government performance and the reality of public service delivery. This study concludes that social media exposure does not holistically reflect successful land governance. The findings highlight a critical policy implication, urging government institutions to shift their digital governance paradigm from a mere public relations tool to an evaluative instrument for responsive public service.   Pemerintah semakin gencar memanfaatkan media sosial untuk membangun citra kelembagaan, namun seringkali terdapat kesenjangan antara narasi institusi dan persepsi publik. Penelitian ini bertujuan menganalisis disparitas topik dan sentimen antara unggahan Instagram Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional (ATR/BPN) dan respons warganet sepanjang tahun 2023. Menggunakan pendekatan kuantitatif, studi ini mengaplikasikan analisis sentimen berbasis leksikon (lexicon-based) dan analisis isi deskriptif terhadap 15.198 komentar dari 1.213 unggahan. Hasil penelitian menyingkap sebuah paradoks komunikasi digital. Sementara agenda institusi didominasi oleh selebrasi kinerja penyerahan sertipikat dan kunjungan kerja menteri, 56,5% komentar warganet justru bersentimen negatif. Warganet secara aktif mengalihfungsikan ruang komentar menjadi wadah pengaduan sengketa agraria, hambatan prosedur administrasi, hingga pelaporan indikasi mafia tanah. Terdapat benturan pemaknaan diametral pada leksikon "tanah" dan "sertipikat" antara glorifikasi kinerja pemerintah dan realitas layanan publik di akar rumput. Studi ini menyimpulkan bahwa eksposur media sosial belum merefleksikan keberhasilan tata kelola pertanahan secara holistik. Implikasi dari temuan ini menuntut institusi pemerintah untuk menggeser paradigma tata kelola digital dari sekadar instrumen kehumasan (public relations) menjadi instrumen evaluasi pelayanan publik yang responsif.